1962
DOI: 10.1021/bi00907a022
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Oxidation-Reduction Potentials and Endogenous Co-factors in Bacterial Photophosphorylation*

Abstract: Rhodospirillum rubnim cell suspensions, disrupted by sonication, yield chromatophores which can be depleted by washing to give minimal photophosphorylation and dark-phosphorylation rates. Photophosphorylation by such chromatophores can be restored to a maximal rate by an optimal concentration of ascorbate (4.7 X 10-8 m) added externally. The same maximal rate is obtained by addition of phenazine methosulfate or by addition of endogenous co-factors, either lumped together in a "supernatant fraction" (chromatoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

1962
1962
1977
1977

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…(81), who showed with ferredoxin cyclic phosphorylation that ATP was formed only while the ferredoxin was in an intermediate redox level. These observations extend to the chloroplast system and point up the previously emphasized im portance of the maintenance of a redox balance or "poising" in bacterial cyclic photophosphorylation (42,48,74,104,169). Many apparent discor dant observations previously noted may have been a result of insufficient appreciation of the importl;l-nce of the maintenance of a proper redox level during the reaction.…”
supporting
confidence: 54%
“…(81), who showed with ferredoxin cyclic phosphorylation that ATP was formed only while the ferredoxin was in an intermediate redox level. These observations extend to the chloroplast system and point up the previously emphasized im portance of the maintenance of a redox balance or "poising" in bacterial cyclic photophosphorylation (42,48,74,104,169). Many apparent discor dant observations previously noted may have been a result of insufficient appreciation of the importl;l-nce of the maintenance of a proper redox level during the reaction.…”
supporting
confidence: 54%
“…The place assigned cytochrome c2-between RHP or flavin-mediated RHP-reductase and bacteriochlorophyll-is based on its high oxidation potential (midpoint potential, pH 7, approximately 330 mv)-and evidence based on our studies of photophosphorylation (Horio and Kamen, 1962) which show clearly it is at the terminal end of the electron transport chain coupled to photophosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatium contains large amounts of RHP (Bartsch and Kamen, 1960), and, as a strict anaerobe, has no requirement for an oxidase, although it shows weak oxidase activity in cell-free extracts (Kamen and Vernon, 1954). Horio and Kamen (1962) have shown that in R. rubrum chromatophores RHP acts as an intermediate in phosphorylation coupled to the photoactivated transport of electrons.…”
Section: Discussionmentioning
confidence: 99%
“…In the cyclic photosynthetic electron transport of R. rubrum, PMS could accept electrons from an early reductant such as flavoprotein since o-phenanthroline, which inhibits the cyclic photophosphorylation in the physiological system, does not inhibit the PMS-mediated phosphorylation [25]. Although ubiquinone-10, flavoprotein, and rhodospirillum heme protein have been shown to be involved in cyclic electron transport and photophosphorylation in R. rubrum, the exact sequence of these electron transport carriers is not known [1,11,21].…”
Section: Discussionmentioning
confidence: 99%